Epidemiology and risk factors of hypovitaminosis D in a cohort of internationally adopted children: a retrospective study - Gilda Salerno; Manuela Ceccarelli; Chiara de Waure; Marianna D’Andrea; Danilo Buonsenso; Valerio Faccia; Davide Pata; Piero Valentini (Italian Journal of Pediatrics, 2018)
Abstract Background Predictors of hypovitaminosis D were extensively studied in the adult population, leading to an approximately complete understanding of them, while there is a lack of studies in the pediatric population, especially in migrant and internationally adopted children. In this retrospective study, we tried to identify the major laboratory predictors of hypovitaminosis D in a cohort of internationally adopted children. Methods Data were extracted from the database of the “Ethnopediatrics Outpatient Clinic” of the “A. Gemelli” Foundation University Hospital in Rome, Italy. Our study included 873 children evaluated from March 2007 to May 2016. Analysis of variance, chi square test, t test and multivariate logistic regression were performed, a “p” value < 0.05 was considered significant, with a confidence interval of 95%. Results We did not find any significant correlation between Vitamin D and Calcium, Phosphates or Magnesium levels within the population we examined. Moreover, parathyroid hormone is not a good predictor of Vitamin D Status. Conclusions Considering the strong influence Vitamin D status has not only on bone health, but also on general well-being, it is due to perform a vitamin D assessment as soon as possible, especially in internationally adopted children.